Revision of the subgenus Dufourea (Flavodufourea) Ebmer, 1984 (Hymenoptera, Halictidae, Rophitinae) and description of a new species D.(Flavodufourea) ulkenkalkana sp.nov. from Kazakhstan - Patiny, Sebastien (Zootaxa, 2003)
Flavodufourea Ebmer, 1984 was described on the basis of D. flavicornis Friese, 1913. The females of this species are actually still unknown and this taxon is the only one included in the subgenus Flavodufourea. Moreover the generic attribution of Flavodufourea to Dufourea Lepeletier, 1841 or Rophites Spinola, 1808 constitutes an unresolved problem. Both sexes of a new Flavodufourea species, D. (Flavodufourea) ulkenkalkana sp.nov., are described here. This description also provides an opportunity to discuss the systematic position of Flavodufourea on a morphological basis.